The Development of a Monoclonal Antibody Recognizing the Drosophila melanogaster Phosphorylated Histone H2A Variant (?-H2AV). - Lake, C.M.; Holsclaw, J.K.; Bellendir, S.P.; Sekelsky, J.; Hawley, R.S. (G3 : genes - genomes - genetics, 2013)
The recognition of DNA double-strand breaks (DSBs) using a phospho-specific antibody to the histone 2A variant has become the gold standard assay for DNA damage detection. Here we report on the development of the first monoclonal antibody to the phospho-specific form of Drosophila H2AV and characterize the specificity of this antibody to programmed DSBs in oocytes and rereplication sites in endocycling cells by immunofluorescence assays and to DSBs resulting from irradiation in both cell culture and whole tissue by Western blot assays. These studies show that the antibody derived in the study is highly specific for this modification that occurs at DSB sites, and therefore will be a new useful tool within the Drosophila community for the study of DNA damage response, DSB repair, meiotic recombination and chemical agents that cause DNA damage.